The Problem of the Priority of the Complete Cause over the Effect from Sayyid Sharif al-Jurjani to Tashkopr?z?de - Huseyni, Zeynelabidin (Şırnak Univ, 2025)
This article examines the issue of the priority of the complete cause over the effect, which expresses the sufficiency and necessity of the cause for the effect. Different approaches to the nature of the complete cause have led to the priority of the complete cause and the posteriority of the effect becoming a controversial issue. In particular, the fact that complete and incomplete causes are expressed as the whole or part of what the effect needs, and that the relationship between the simple and compound complete cause and the effect differs, forms the basic background to this issue. Indeed, the fact that the formal and material parts, which are among the types of causes required by the composite effect, are both elements of the complete cause and constitute the nature of the effect has led to the problematisation of the priority of the complete cause over the effect. The importance given to the nature of complete and incomplete causes, as well as the issue of their priority over the effect, stems from their connection to many metaphysical issues, such as the proof of God. Sayyid Sharif al-Jurjani (d. 816/1413) addressed the issue of the priority of the complete cause over the effect in his works & Sacute;arh al-Maw & amacr;qif and H & amacr;shiyyat al-Tajr & imacr;d and presented his solution to it. He ensured the continuity of the search for answers to this question in the Ottoman intellectual world after him, accompanied by different approaches. Among those who quoted Jurjani's question and provided answers were H & imath;z & imath;r Bey (d. 863/1459), Sin & amacr;n P & amacr;sh & amacr; (d. 891/1486), Khojaz & amacr;da (d. 893/1488), Mull & amacr; Lutf & imacr; (d. 900/1495), Qara Sayd & imacr; (d. 912/1507), Kamalpashaz & amacr;dah (d. 940/1534), and Tashkopr & imacr;z & amacr;de (d. 968/1561). The common point among these figures is that they sought to respond to the philosophical issues raised by Jurjani with acceptance, rejection, or correction, and that they were also critical of each other. In this study, the development of the issue of the priority of the complete cause over the effect from Jurjani to Tashkopr & imacr;z & amacr;de is addressed comparatively based on available data and names.
Keywords: Islamic Philosophy; Causality; Complete Cause; Priority- Posteriority; Sayyid Sharif al-Jurjani; Tashkopr & imacr;z & amacr;de